Expression patterns of inflorescence‐ and sex‐specific transcripts in male and female inflorescences of African oil palm (Elaeis guineensis). (28th December 2015) - Ho, H.; Low, J. Z.; Gudimella, R.; Tammi, M. T.; Harikrishna, J. A.
Abstract: Oil palm is a monoecious plant and the sex ratio of the female to male inflorescences on each palm is important for breeding and commercial production.We hypothesise that the sex differences of oil palm inflorescences are due, at least in part, to variations in gene expression so this study aimed to establish the sexual differences by using whole genome expression analysis. We sequenced the transcriptomes of oil palm male and female inflorescences at the earliest stage at which the male and female tissues can be reliably distinguished. From the transcriptome data, we identified 97 potential sex‐specific transcripts. Among the validated transcripts, oil palm orthologs of acid phosphatase and DEFICIENS showed male‐specific expression patterns whereas orthologs of bZIP transcription factor, late embryogenesis abundant protein and TASSELSEED1 showed female‐specific expression patterns. Transcripts for orthologs of acid phosphatase and late embryogenesis abundant protein were also strongly inflorescence‐specific. Furthermore, we assembled a broad and dense consensus transcriptome from male and female inflorescences, shoot apical meristem, mesocarp, leaf and root of oil palm, which provides a valuable reference for identification of unique and common transcripts between these tissues. We suggest that the combined expression of inflorescence‐ and sex‐specific transcripts may account for sexual differences of oil palm male and female inflorescences.